2000
DOI: 10.1038/35019082
|View full text |Cite
|
Sign up to set email alerts
|

Mice overexpressing human uncoupling protein-3 in skeletal muscle are hyperphagic and lean

Abstract: Uncoupling protein-3 (UCP-3) is a recently identified member of the mitochondrial transporter superfamily that is expressed predominantly in skeletal muscle. However, its close relative UCP-1 is expressed exclusively in brown adipose tissue, a tissue whose main function is fat combustion and thermogenesis. Studies on the expression of UCP-3 in animals and humans in different physiological situations support a role for UCP-3 in energy balance and lipid metabolism. However, direct evidence for these roles is lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
463
2
9

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 562 publications
(505 citation statements)
references
References 22 publications
31
463
2
9
Order By: Relevance
“…That this increase in energy expenditure is directly related to the tumour effect is evidenced by the fact that removal of tumour ensures prompt restoration of normal metabolism (Luketich et al, 1990). UCP-3, when overexpressed in the skeletal muscle of transgenic mice results in a lean phenotype, with increased energy expenditure compared to controls (Clapham et al, 2000). Over expression of UCP-3 in the skeletal muscle of human cancer patients might contribute to increase energy expenditure and thus to weight loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That this increase in energy expenditure is directly related to the tumour effect is evidenced by the fact that removal of tumour ensures prompt restoration of normal metabolism (Luketich et al, 1990). UCP-3, when overexpressed in the skeletal muscle of transgenic mice results in a lean phenotype, with increased energy expenditure compared to controls (Clapham et al, 2000). Over expression of UCP-3 in the skeletal muscle of human cancer patients might contribute to increase energy expenditure and thus to weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…Both have uncoupling activity in vitro and may mediate the increased energy expenditure implicated in energy balance. Transgenic mice over-expressing UCP-3 in muscle are lean despite exhibiting hyperphagia; oxygen consumption in the transgenic animals was increased by 91% indicating an increase in metabolic rate (Clapham et al, 2000). The exact roles of the various UCP isoforms in vivo are still debated and are reviewed elsewhere (Ricquier and Bouillaud, 2000).…”
mentioning
confidence: 99%
“…The uncoupling protein 3 (UCP3) is a muscle-specific isoform, which seems to be involved in fat oxidation and regulation of body fat content. 4 It has been demonstrated that fatty acids either in their unesterified form or as part of dietary fats are able to influence a variety of parameters related with energy homeostasis, such as body fat mass, lipid metabolism, thermogenesis, and food intake. For example, consumption of fish oil, whose major lipid components are the polyunsaturated fatty acids eicosapentaenoic and docosahexaenoic acid with a chain length of 20 and 22 carbon atoms, respectively, decreased total body fat in Wistar rats.…”
Section: Introductionmentioning
confidence: 99%
“…Although none of the UCP ±/± mice (1, 2 or 3) is obese [10, 48, 111, 140, 141] it remains to be determined how UCP2 interacts with other potential energy monitoring molecules to participate in weight homeostasis. Of interest are data showing that mice with skeletal muscle-specific induction of UCP3 have decreased body weight despite normal [142] or increased food intake [143]. The metabolic rate is increased, as is insulin sensitivity and glucose uptake, whereas adipose tissue mass is reduced by about 50 % [143].…”
Section: Relation Of Ucp2 With Metabolic Diseasesmentioning
confidence: 99%
“…Of interest are data showing that mice with skeletal muscle-specific induction of UCP3 have decreased body weight despite normal [142] or increased food intake [143]. The metabolic rate is increased, as is insulin sensitivity and glucose uptake, whereas adipose tissue mass is reduced by about 50 % [143].…”
Section: Relation Of Ucp2 With Metabolic Diseasesmentioning
confidence: 99%